Short-Term High Fat Intake Does Not Significantly Alter Markers of Renal Function or Inflammation in Young Male Sprague-Dawley Rats - Catherine Crinigan; Matthew Calhoun; Karen L. Sweazea (Journal of Nutrition and Metabolism)
Chronic high fat feeding is correlated with diabetes and kidney disease. However, the impact of short-term high fat diets (HFD) is not well-understood. Six weeks of HFD result in indices of metabolic syndrome (increased adiposity, hyperglycemia, hyperinsulinemia, hyperlipidemia, hyperleptinemia, and impaired endothelium-dependent vasodilation) compared to rats fed on standard chow. The hypothesis was that short-term HFD would induce early signs of renal disease. Young male Sprague-Dawley rats were fed either HFD (60% fat) or standard chow (5% fat) for six weeks. Morphology was determined by measuring changes in renal mass and microstructure. Kidney function was measured by analyzing urinary protein, creatinine, and hydrogen peroxide (H2O2) concentrations, as well as plasma cystatin C concentrations. Renal damage was measured through assessment of urinary oxDNA/RNA concentrations as well as renal lipid peroxidation, tumor necrosis factor alpha (TNFα), and interleukin 6 (IL-6). Despite HFD significantly increasing adiposity and renal mass, there was no evidence of early stage kidney disease as measured by changes in urinary and plasma biomarkers as well as histology. These findings suggest that moderate hyperglycemia and inflammation produced by short-term HFD are not sufficient to damage kidneys or that the ketogenic HFD may have protective effects within the kidneys.